A duty cycle division multiplexing with amplitude distribution controller transmitter - Abas @ Ismail, Ahmad Fauzi; Mahdiraji, Ghafour Amouzad; Ibrahim, Noor Hisyam (2011)

(untitled)
The present invention generally relates to a duty cycle division multiplexing for optical communication systems. The duty cycle division multiplexing comprises of a transmitter with an amplitude distribution controller wherein said amplitude distribution controller is provide to control the amplitude distribution of the duty cycle division multiplexing.